Sharia compliance and competitive advantage in Small and Medium Enterprises: The mediating role of digital payment usage - Ramashar, Wira; Khairunnisa, Saskia (Journal of Accounting and Investment, 2025)
Research aims: This study aims to investigate the influence of religious knowledge, religious motivation, and Sharia compliance on competitive advantage among Small and Medium Enterprises (SMEs) in the coffee shop sector in Pekanbaru City, with digital payment system usage as a mediating variable.Design/Methodology/Approach: Using a quantitative approach, data were collected from 147 coffee shop SMEs operating in Pekanbaru, Riau Province. Structural Equation Modeling (SEM-PLS) was employed to analyze the direct and indirect relationships among variables.Research findings: The results indicate that religious knowledge, religious motivation, and Sharia compliance have a significant positive impact on both competitive advantage and the digital payment system usage. Furthermore, the digital payment system usage also significantly enhances competitive advantage. Sharia compliance also exerts an indirect effect on competitive advantage through the mediation of digital payment system usage.Theoretical contribution/ Originality: This research extends the Resource-Based View (RBV) by positioning Sharia compliance as a unique, valuable, and inimitable resource that contributes to sustainable competitive advantage in the Islamic business context. It also highlights the strategic role of digital transformation in religiously motivated business ecosystems. Practitioner/Policy implication: The findings provide valuable insights for policymakers and business practitioners on the importance of embedding religious and ethical values within strategic business practices, particularly in the halal food and beverage sector. Promoting digital adoption within a Sharia-compliant framework can enhance competitiveness among SMEs.Research limitation/Implication: This study is limited to coffee shop SMEs in one city and does not account for variations in business scale or experience. Future research should explore other sectors and regions using mixed methods for deeper insights.